FAMILY LINGUISTIC PRACTICES AND THE DEVELOPMENT OF THEORY OF MIND IN EARLY CHILDHOOD EDUCATION: A THEORETICAL REVIEW (REMUNOM, 2026)
This theoretical article discusses the relationship between linguistic practices and the development of false-belief understanding in children, considering its implications for the development of Theory of Mind. Theory of Mind refers to the ability to attribute mental states—such as beliefs, desires, intentions, and emotions—to oneself and to others, enabling the interpretation and prediction of behavior in social contexts. Research in the field of developmental psychology indicates that this ability emerges gradually during childhood and is strongly associated with the social and linguistic experiences children encounter. Family and school interactions that involve conversations about thoughts, feelings, and intentions tend to foster the construction of an understanding of mental states. The article presents a literature review that integrates classical and contemporary studies on Theory of Mind, sociocognitive development, and the role of language in social interactions. It also discusses how linguistic practices that emphasize mentalistic terms may promote the development of false-belief understanding. Finally, pedagogical implications for Early Childhood Education are presented, highlighting the role of linguistic interactions, narratives, and symbolic play in promoting children’s sociocognitive development.